A hódmezővásárhelyi országgyűlési képviselőválasztások 1939-ben - Zeman, Ferenc (Közép-Európai Közlemények, 2014)
In the Pentecost of 1939 there was the general election in Hungary. The vote passed off by the new electoral law, which was made in 1938. In the city of Hódmezıvásárhely the election – which was secret and made with party lists – was held from May 28 to 29. In the course of the campaign four parties managed to have enough recommendations: the Party of Hungarian Life (with Miklós Bonczos under-secretary of state), the Social Democratic Party (with the leadership of Ferenc Takács), the Independent Smallholders Party (with the leadership of Béla Kun) and the National Front (with the leadership of Mátyás Matolcsy), which caused a big surprise. In the course of the campaign all of the parties attacked each other, and of course they promised a lot. The winner of the election was the Party of Hungarian Life and also the second mandate was owned by the party of the government. Miklós Bonczos was elected in an other place, too, that is why he resigned the mandate. Imre Temesváry and János Lénárt – who before was on the second and on the third place of the list of the party of the government – became the parliamentarian of the city.